High Origin and Superficial Course of Ulnar Artery: A Case Report - Krıshnamurthy, Ashwin; Kumar, Madhan; Nayak, Soubhagya Ranjan; Prabhu, Latha Venkatraya (Fırat University, 2006)
Variations in the arterial system of the upper limb are well documented. During routine dissection of the right upper limb of a 60-year-old female cadaver, a superficial ulnar artery was noted. The ulnar artery had a high origin from the brachial artery in the middle of the arm and proceeded superficially in the forearm but had a normal termination in the hand. The common interosseous artery arose as a terminal branch of the brachial artery at the level of the neck of the radius. Reports of high origin of ulnar artery have been cited in the literature but what made this case different from others was its association with normal musculature in the forearm. Superficial position of the ulnar artery make them more vulnerable to trauma and to haemorrhage but at the same time more accessible for cannulation, if need be. Embryological basis and significance of such an origin has been explained. ©2006, Fırat Üniversitesi, Tıp Fakültesi

Üste ekstremite arteryel varyasyonları sıkça bildirilmiştir. Rutin diseksiyon çalışması sırasında sağ üst ekstremite de 60 yaşında bir kadın kadavrada yüzeysel unlar artere rastlanmıştır. Bu unlar arter kolun orta kısmında brakial arterden yüksek orijinli olup, ön kolda yüzeysel seyrederek elde normal lokalizasyon da sonlanmaktaydı. İnterossöz arter radius boynu hizasında brakial arterin terminal dalı olarak ortaya çıkar. Yüksek orijinli unlararter literatürde bildirilmiştir, olgumuzu nadir kılan bu arterin ön kol normal kas yapılarıyla olan ilişkisidir. Yüzeysel ulnar arterler travmalara ve kanamalara karşı hassas yapılardır ancak gerektiğinde kanül yerleştirilmesi kolaydır. Bu tip bir orijinin embryolojik temeli ve önemi açıklanmıştır.©2006, Fırat Üniversitesi, Tıp Fakültesi
Yüksek Orijinli Yüzeysel Seyirli Ulnar Arter: Olgu Sunumu